Penyelesaian Assignment Problem Dengan Menggunakan Metode Program Dinamis: (Studi Kasus : CV. Sinar Utama) - Karundeng, Franklin Peter Anton; Purnamasari, Ika; Yuniarti, Desi (EKSPONENSIAL, 2021)
Assignment problem that maximize profits or minimize time, distance and cost by placing the appropiate workforce with ability. Solving the assignment problem can be done by dynamic program method. To apply the dynamic program method the number of sources assigned should be equal to the number of tasks to be completed.Otherwise each source should be assigned only for one task. The purpose of this study is to determine the minimum total time of completion of work and know the assignment of employees has been optimal. The data used is the time of assignment of employees completing the work on the worksop in showroom CV. Sinar Utama of Samarinda. From the analysis result using dynamic program method obtained by total completion time of 85 minutes and by looking at the comparison before and after using dynamic program method that total employee assignment time by using dynamic program method equal to 257 minutes and before using dynamic program method that is equal to 530 minutes. It can be concluded that the total minimum work completion time of 85 minutes and based on the comparison before and after using the dynamic program method idicates that the assignment of employee has been optimal.